2012
DOI: 10.1017/s2045796012000716
|View full text |Cite
|
Sign up to set email alerts
|

Call for information, call for quality in mental health care

Abstract: The quality of routine mental health care is not optimal, it can vary greatly from region to region and among providers; in many occasions, it does not correspond to the standards of evidence-based mental health. To bridge this gap, the promotion of a systematic use of the information available for quality assurance would be most helpful, but measuring the quality of mental health care is particularly challenging. Quality measurement can play a key role in transforming health care systems, and the routine meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…Data on help‐seeking decision and first therapy setting did not show significant differences across epochs of onset, but they revealed that an autonomous decision to seek help tended to be less frequent, compared to that influenced and/or taken by others. This finding stresses the importance of correct and updated information outside the community of patients with mental disorders, in order to facilitate treatment access and implement early intervention programs . Data on first therapy setting simply indicate that the outpatient setting tends to account for approximately four out of five cases, with no difference over time.…”
Section: Discussionmentioning
confidence: 89%
“…Data on help‐seeking decision and first therapy setting did not show significant differences across epochs of onset, but they revealed that an autonomous decision to seek help tended to be less frequent, compared to that influenced and/or taken by others. This finding stresses the importance of correct and updated information outside the community of patients with mental disorders, in order to facilitate treatment access and implement early intervention programs . Data on first therapy setting simply indicate that the outpatient setting tends to account for approximately four out of five cases, with no difference over time.…”
Section: Discussionmentioning
confidence: 89%
“…Because the National Health Information System is undergoing implementation, in the near future, we should benefit by a core set of indicators helping to evaluate processes and outcomes across regions and providing information on the epidemiological characteristics of regional MH systems (Lora, 2013;Lora et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of providing and receiving correct information at the right level and time is described in a previous study, which reviewed evidence on the quality of information transfer between primary care physicians and specialist mental health providers for referral and after inpatient discharge. Previous research has also revealed variability in the quality of protocols in mental health care, with differences existing between regions and among providers and, in some cases, a lack of correspondence between the provided care and the standards of evidence‐based mental health care …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has also revealed variability in the quality of protocols in mental health care, with differences existing between regions and among providers and, in some cases, a lack of correspondence between the provided care and the standards of evidencebased mental health care. 32 Participants emphasized the need for new evidence-based protocols for the patient discharge process. One staff member succinctly expressed this shared sentiment when she made the following remark:…”
Section: Integrated Carementioning
confidence: 99%